A SEMANTIC ANALYSIS OF DEIXIS IN DRAMA WRITTEN BY LUCILLE FLETCHER - Sukasih Ratna Widayanti; Suhud Eko Yuwono (Lire Journal (Journal of Linguistics and Literature), 2019)
This study purposes to describe the forms of deixis in the drama written by Lucille Fletcher. This is descriptive qualitative study. The sources of the data are in the form of word and phrase in the drama script written by Lucille Fletcherentitled Sorry, Wrong Number. Based on the data findings, the form of deixis in the drama script Lucille Fletcher’s Sorry, Wrong Number are the person deixis, place deixis, time deixis, and social deixis. The highest occurrence on the forms of deixis in Lucille Fletcher’s Sorry, Wrong Number is person deixis. It means that person deixis is the most common type used by the characters in Lucille Fletcher’s Sorry, Wrong Number to communicate between each character in order to deliver their message due to the plot of the drama.